HflX-mediated drug resistance through ribosome splitting and rRNA disordering in mycobacteria - Soneya Majumdar; Amuliya Kashyap; Ravi K. Koripella; Manjuli R. Sharma; Kelley Hurst-Hess; Swati R. Manjari; Nilesh K. Banavali; Pallavi Ghosh; Rajendra K. Agrawal (Proceedings of the National Academy of Sciences, 2025)
HflX is a highly conserved ribosome-associated GTPase implicated in rescuing stalled ribosomes and mediating antibiotic resistance in several bacteria, including macrolide-lincosamide antibiotic resistance in mycobacteria. Mycobacterial HflXs carry a distinct N-terminal extension (NTE) and a small insertion, as compared to their eubacterial homologs. Here, we present several high-resolution cryo-EM structures of mycobacterial HflX in complex with the 70S ribosome and its 50S subunit, with and without antibiotics. These structures reveal a distinct mechanism for HflX-mediated ribosome splitting and antibiotic resistance in mycobacteria. Our findings indicate that the NTE of mycobacterial HflX induces persistent disordering of multiple 23S rRNA helices, facilitating the dissociation of the 70S ribosome and generating an inactive pool of 50S subunits. During this process, HflX undergoes a large conformational change that stabilizes its NTE. Mycobacterial HflX also acts as an anti-association factor by binding to predissociated 50S subunits. Our structures show that a mycobacteria-specific insertion in HflX reaches far into the peptidyl transferase center (PTC), such that it would overlap with the ribosome-bound macrolide antibiotics. However, in the presence of antibiotics, this insertion retracts, adjusts around, and interacts with the antibiotic molecules. These results suggest that mycobacterial HflX is agnostic to antibiotic presence in the PTC. It mediates antibiotic resistance by splitting antibiotic-stalled 70S ribosomes and inactivating the resulting 50S subunits.